Establishing responsible use of AI guidelines: a comprehensive case study for healthcare institutions - Agustina D. Saenz; Mass General Brigham AI Governance Committee; Amanda Centi; David Ting; Jacqueline G. You; Adam Landman; Rebecca G. Mishuris (npj Digital Medicine)
Abstract This report presents a comprehensive case study for the responsible integration of artificial intelligence (AI) into healthcare settings. Recognizing the rapid advancement of AI technologies and their potential to transform healthcare delivery, we propose a set of guidelines emphasizing fairness, robustness, privacy, safety, transparency, explainability, accountability, and benefit. Through a multidisciplinary collaboration, we developed and operationalized these guidelines within a healthcare system, highlighting a case study on ambient documentation to demonstrate the practical application and challenges of implementing generative AI in clinical environments. Our proposed framework ensures continuous monitoring, evaluation, and adaptation of AI technologies, addressing ethical considerations and enhancing patient care. This work contributes to the discourse on responsible AI use in healthcare, offering a blueprint for institutions to navigate the complexities of AI integration responsibly and effectively, thus promoting better, more equitable healthcare outcomes.